ASSESSMENT AND ANALYSIS OF DIGITAL TRANSFORMATION OF REGIONAL ECONOMIC SYSTEMS OF THE RUSSIAN FEDERATION: METHODOLOGICAL APPROACHES AND THEIR APPROBATION - M. R. Safiullin; A. A. Abdukaeva; L. A. Elshin (Вестник университета, 2020)
Monitoring and evaluating the quality of digitalization of the socio-economic environment at both thenational and regional levels, contribute to an understanding of the potential for its sustainable and competitive development as part of the global economy entering the wake of the digital transformation of economic processes. In this regard, studies aimed at studying such issues are very relevant and significant for modern science and practice. The article proposes an algorithm for measuring the level of development of the content elements of the digital economy in the regions of the Russian Federation. A distinctive aspect of the proposed algorithm is the orientation of the developed tools to study the five main directions of digitalization, defined by the Order of the Government of the Russian Federation of July 28, 2017 (No. 1632-r): regulatory regulation, personnel for the digital economy, formation of research competencies and technological foundations, information infrastructure, information security. Based on the results of the study, the main qualitative and quantitative characteristics have been identified, that assess the development of the digital economy in the constituent entities of the Russian Federation at the present stage of development; a toolkit has been offered, that allows you to determine key areas of regional policy aimed at intensifying the processes of digitalization of business processes.